INTERNAL TESTING RESULT MANAGEMENT SYSTEM: (Studi Kasus: PT. Solmit Bangun Indonesia) - Rini Nuraini Sukmana; Abdurrahman; Karina Khairiyyah (LPPM STMIK Bandung, 2021)
One of the most important stages in the software development process is the testing phase. Tests on the software are performed with the aim of ensuring the functions of the software are working properly. PT. Solmit Bangun Indonesia as a company engaged in information technology services has obligations to it is clients to provide the best service by producing a software product that suits the needs. One effort made to ensure the software product has been running properly and as needed is the implementation of a system that can manage and monitor bugs in the software. Internal testing result management system is a system that helps the management and monitoring of data resolving issues (bugs) on software both in development stage and that have been implemented. The methodology used in this study is the method of by using Unified Modeling Language (UML) as a modeling language. For the development of the system using the prototype method. The programming language used in the design of this system is PHP Hypertext Preprocessor which is built using the framework code igniter (CI) with MySQL database. The thing that has been achieved in this research is has made a system that assist in managementand monitoring of solution of issues (bugs) in software at PT. Solmit Bangun Indonesia.